FACILITY ASSESSMENT FOR MATERNAL AND CHILD HEALTH SERVICES IN BANGLADESH USING SERVICE AVAILABILITY AND READINESS ASSESSMENT (SARA) TOOL: A CROSS-SECTIONAL PILOT STUDY - Aftab, Afzal; Hasan, Mehedi; Bari, Rahmatul; Hossain, Mohammad Didar; Hasan, Mehadi; Azad, Abul Kalam; Islam, Bulbul; Sarker, Malabika (YCAB Publisher & IAKMI SULTRA, 2017)
Background: To initiate journey towards the Universal Health Coverage (UHC) it is essential to assess the health facilities. Unfortunately, no health facility assessment has been conducted in Bangladesh so far using